Studi Kelayakan Investasi Pengadaan Loader Dan Hauler Untuk Alternatif Beli Langsung Pada Kegiatan Coal Hauling Dari Rom PIT Ke Rom Port PT. MNC Infrastruktur Utama Jobsite PT. Bhumi Sriwijaya Perdana Coal, Provinsi Sumatera Selatan - wahyuzanora wahyuzanora; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2023)
Abstract.  PT. Bhumi Sriwijaya Perdana Coal (PT. BSPC) is a company engaged in coal mining located in Beji Mulyo Village, Tungkal Jaya District, Musi Banyuasin Regency, South Sumatra Province. PT. BSPC is a company that owns a Mining Business Permit (IUP) with an IUP area of 6.866 Ha, reserves of 39.401.487 tons of coal with a stripping ratio of 1:2.7. PT. BSPC plans to build a hauling road and procure equipment. This study aims to examine the feasibility of investing in the procurement of loaders and haulers, as well as alternative equipment procurement that is profitable for the company.The investment feasibility in the procurement of equipment with direct purchase alternatives using the NPV, IRR and Payback Period. The alternative is to buy directly with an NPV value of IDR 47.549.034.507, an IRR of 51% and a long return on investment of 1,8 years.Based on the sensitivity analysis that the researchers did, it was found that the BEP value for the direct purchase alternative was IDR 33.011.Keywords: Productivity, Loader, Hauler, Match Factor